Perancangan Sistem Infomasi Penjadwalan Kegiatan Pada KPU Berbasis Web - Ade Risky Pradika; Muhammad Dedi Irawan (LKP Unity Academy, 2024)
Scheduling is a classic and commonly encountered issue. Various institutions are currently facing scheduling problems concerning their employees or staff, one of which involves the scheduling of activities at the Electoral Commission (KPU). However, KPU presently relies on a manual system without a structured database system, leading to delays in completing tasks that should ideally be finished on time and making the process vulnerable to errors. To address this, the waterfall method is being utilized for system development, encompassing stages such as system requirement analysis, system design, system development, system testing, and system implementation. The subsequent application is being developed using PHP and MYSQL. The implementation of this scheduling information system aims to facilitate KPU employees in efficiently carrying out their daily tasks and activities, thereby streamlining the scheduling process. By presenting the results of this research, it is expected that the design of the web-based activity scheduling information system for the Election Commission (KPU) can positively contribute to the efficiency and effectiveness of KPU's tasks related to general elections.